Sistem Kontrol Cerdas berbasis Internet of Things pada Pertanian Lahan Kering: Peluang dan Tantangan di Pulau Timor - Erniati, Erniati; Laumal, Folkes E.; Hattu, Edwin P.; Lapinangga, Nina J. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Dryland farming in tropical climates, such as Timor Island, East Nusa Tenggara, faces numerous challenges, including low and variable rainfall, limited water resources, and soil degradation. Intelligent control technology and the Internet of Things (IoT) offer innovative solutions to address these challenges through environmental monitoring and control in agricultural systems, aiming to improve efficiency and productivity. This study aims to examine the opportunities and challenges of developing relevant IoT-based intelligent control systems, as well as potential solutions for managing dryland farming with IoT applications. The research is conducted through a literature review of dryland farming conditions and the challenges of using IoT applications, environmental condition monitoring of dryland using IoT devices, and identifying the strengths, weaknesses, opportunities, and threats of using intelligent IoT-based applications. The research findings indicate that the dominance of dryland, combined with low water availability, requires optimal agricultural irrigation management while still maximizing plant growth and productivity. The application of intelligent technology for real-time monitoring and control is essential for managing the climate in dryland areas, representing an opportunity amid the challenges of managing horticultural dryland farming. These research results also serve as a reference for the development and implementation of IoT-based intelligent technology control in the dryland farming sector.